The great recession of 2008-2009: causes, consequences and policy responses - Verick, Sher; Islam, Iyanatul (Bonn, 2010)
"Starting in mid-2007, the global financial crisis quickly metamorphosed from the bursting of the housing bubble in the US to the worst recession the world has witnessed for over six decades. Through an in-depth review of the crisis in terms of the causes, consequences and policy responses, this paper identifies four key messages. Firstly, contrary to widely-held perceptions during the boom years before the crisis, the paper underscores that the global economy was by no means as stable as suggested, while at the same time the majority of the world’s poor had benefited insufficiently from stronger economic growth. Secondly, there were complex and interlinked factors behind the emergence of the crisis in 2007, namely loose monetary policy, global imbalances, misperception of risk and lax financial regulation. Thirdly, beyond the aggregate picture of economic collapse and rising unemployment, this paper stresses that the impact of the crisis is rather diverse, reflecting differences in initial conditions, transmission channels and vulnerabilities of economies, along with the role of government policy in mitigating the downturn. Fourthly, while the recovery phase has commenced, a number of risks remain that could derail improvements in economies and hinder efforts to ensure that the recovery is accompanied by job creation. These risks pertain in particular to the challenges of dealing with public debt and continuing global imbalances. "